1986
DOI: 10.1203/00006450-198611000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Micropuncture Measurement of Lung Microvascular Pressure Profile in 3- to 4-Week-Old Rabbits

Abstract: ABSTRACT. We have reported the longitudinal distribution of vascular resistance in the three segments (arteries, microvessels, and veins) of the pulmonary circulation of adult rabbits (J Appl Physiol 60:539-545, 1986). To determine the longitudinal distribution of vascular resistance in lungs of younger animals, we measured microvascular Dressures in the sub~leural microcirculation in nine isolated blood perfused lungs of 3-to 4-wk-old rabbits. We used micropipettes and the servonull pressure measuring system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Although in the adult lung, much of the resistance is in the microvascular segment, in the young human and in young rabbits, pulmonary vascular resistance has been shown to reside mainly in the arteries and veins, with a shift to the microvascular segment occurring with increasing age (14). Structural and pharmacological changes in response to chronic hypoxia are similar in large muscular and resistance arteries (10,15).…”
mentioning
confidence: 79%
“…Although in the adult lung, much of the resistance is in the microvascular segment, in the young human and in young rabbits, pulmonary vascular resistance has been shown to reside mainly in the arteries and veins, with a shift to the microvascular segment occurring with increasing age (14). Structural and pharmacological changes in response to chronic hypoxia are similar in large muscular and resistance arteries (10,15).…”
mentioning
confidence: 79%
“…He also found that this effect was exaggerated in the presence of red blood cells. In our study, the osmolarity of the perfusates ranged from 265 to 340 mosm/l, and in group 5, 6, and 7 In general, the effect of an increase in blood flow and total arteriovenous pressure drop is a decrease in pulmonary vascular resistance that is mainly due to vascular distension and recruitment. Some of the reduction in total resistance is also due to a reduction in apparent viscosity of blood.…”
Section: Effect Of Dextran-induced Increases In Perfusate Viscosity Omentioning
confidence: 56%
“…We accepted p<0.05 as indicative of statistical significance. 7. In group 7 lungs, at the lower flow rate (30+7 ml* kg`.…”
Section: Data Analysesmentioning
confidence: 93%
“…A predominant ar terial resistance in lungs of younger animals has been described in some species [15][16][17], consistent with morphometric findings of a thicker smooth muscle coat in pulmonary ar teries in the neonatal period with a decrease in muscle mass and increase in vessel luminal diameter with increasing age [10,20]. How ever, we did not find any differences in the vascular pressure profile in lungs of 2-to 3-week-old, 5-to 6-week-old and adult ferrets, making this explanation unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that in the fer ret, the longitudinal distribution of segmental vascular resistance in the lung is similar in neonatal, juvenile and adult ferrets [19], un like the rabbit in which the contribution of arteries, microvessels and veins to total pul monary vascular resistance changes with age [17], Also, in both neonatal and adult ferret lungs, both arteries and veins constrict with hypoxia to the same degree [18]. The mecha nisms of the age-related differences in PTXinduced pulmonary vasodilation are not clear but we can speculate on some possibilities.…”
Section: Age-related Differences In Ptx Effectsmentioning
confidence: 99%